ANALISIS PERAN UMKM DALAM PEREKONOMIAN JAWA TIMUR - Aisyah Aminy (STIE Mahardhika, 2022)
Micro, Small and Medium Enterprises (MSME’s) is a form of economic life of most people who have contributed to the economic growth of East Java with the contribution of East Java's GRDP of 54.98 percent. In the last ten years, MSME experienced a significant growth of 4.2 million in 2006, 6.8 million in 2012, and in 2018 it was 9.78 million businesses. Therefore, in this study an analysis of the value added of cooperatives and MSMEs in East Java in the last 3 (three) years, namely 2016, 2017, and 2018 with the aim to determine the role of cooperatives and MSMEs in the economy of East Java. This type of research is quantitative research with the method used is the analysis of value added based on current prices obtained from the multiplication of the ratio of value added to output while to obtain added value at constant prices using the PDRB Constant method. The results showed that in 2016 the contribution of MSME’s value added to the economy of East Java was 56.43 percent, increasing to 56.63 percent in 2017 and in 2018 also increasing to 56.93 percent.